International development strategies for the XXIst century and post-modern patrimonialism in Africa – Angola and Mozambique - Vidal, N. F. (Revista Brasileira de Política Internacional, 2018)
Development thinking has been progressively dominated by neo-institutionalism, influencing major donors in Africa, and recently included in the UN 2030 Agenda for development. This paper discusses some unintended impacts of such strategies in neo-patrimonial regimes such as Angola and Mozambique, whereby neo-institutionalism favoured donors' apolitical “partnership” with resilient neo-patrimonial structures, facilitating its recycling, sophistication, and modernization, taking advantage of financial globalization to its own ends and improving its democratic image through elections, but leaving untouched the principles of neo-patrimonial political management for a minority to hold on to power since independence. Theoretically, this approach contrasts with varieties of democracy and varieties of capitalism perspectives.